Novel four‐session treatment intervention for anxiety and high‐functioning autism: A single case report for Externalizing Metaphors Therapy. Issue 2 (14th October 2018) - McGuinty, Everett F.; Bird, Brian M.; Nelson, John; McGuinty, Jazlyn L.; Cashin, Andrew
Abstract: Topic: The Brief Services psychotherapy paradigm has evolved to produce cost‐effective and clinically significant outcomes in children's mental health. Though its clinical evaluation is still in its infancy, it has been utilized to a much lesser degree with autism spectrum disorders, which typically require a longer‐term approach to psychotherapy treatment. Purpose: The current paper introduces a novel, four‐session intervention that aims to decrease anxiety experienced by clients presenting with high‐functioning autism. Externalizing Metaphors Therapy is based upon the externalization of problems, transformation of metaphoric imagery, shifting of maladaptive emotional schemas, and the generalization of problems. A case study is utilized to visually aid in the understanding of this new treatment intervention. Source: A composite literature review was conducted with regards to significant works in Narrative Therapy, treatment interventions for anxiety and high functioning autism, evidence‐based treatments for anxiety, and practice based approaches in psychotherapy. Works were selected based on their relevance to the research filed of anxiety and autism. Conclusions: This clinical research challenges the children's mental health field in addressing anxiety and high‐functioning autism from a brief framework. Further clinical research is needed to clinically evaluate the current model.